Coalescent simulations indicate that the São Francisco River is a biogeographic barrier for six vertebrates in a seasonally dry South American forest - Coelho, Felipe Eduardo Alves; Guillory, Wilson Xavier; Gehara, Marcelo (Frontiers in Ecology and Evolution, 2022)
The riverine barrier hypothesis has been extensively explored in Neotropical rainforests, while its importance in drier regions such as the Caatinga, a seasonally dry tropical forest in northeastern Brazil, has only recently received more attention. The Caatinga is bisected by the São Francisco River (SFR), which has long been suggested to be an important biogeographic feature in the region. However, recent studies have found mixed support for the role of the SFR as a hard barrier, most of them relying on the presence or absence of genetic breaks congruent with its course. Here, we used published multilocus and next-generation data from six vertebrate species to test the SFR’s strength as a barrier. Using model-based approaches (approximate Bayesian computation and supervised machine learning), we tested demographic models incorporating full, intermediate, and zero migration across the SFR, estimating divergence times and migration rates for each species. We found support for the SFR’s role as a barrier, allowing gene flow for some species. Estimated divergence times varied among species but are limited to the late Pleistocene, coherent with one of several proposed paleocourse changes in the river’s geological history. Contrary to the mixed results of previous studies, our study supports the SFR as an important phylogeographic barrier across different taxonomic groups, driving diversification in the Caatinga.